Antimicrobial Susceptibility Patterns of Bacterial Isolates from Surgical Site Infections: An Experience from Two Tertiary Level Hospitals in Dhaka City, Bangladesh - Fatema, Syeda Kaniz; Rashed, Asif; Asaduzzaman, Muhammad; Sufrin, Sumaira; Khan, Sharmin Jahan; Nahar, Kamrun; Sultana, Sadia (Mugda Medical College Journal, 2025)
Surgical site infection (SSI) is an infection created by an invasive surgical procedure within 30 days if no prosthetic in situ or 1 year if a prosthetic is implanted in the patient. It is one of the most critical post-operative complications worldwide. A cross-sectional, observational study was conducted, between July 2022 and June 2023, at Dhaka Medical College Hospital and Mugda Medical College Hospital in Dhaka, Bangladesh, to identify causative bacteria of surgical site infections and their antimicrobial susceptibility patterns. Wound infection with cellulitis, no drainage, and suture abscesses were excluded. Demographic and laboratory data of the patients were recorded. Pus samples or wound swabs of clinically suspected SSI cases sent to the Department of Microbiology of the respective hospitals and were inoculated and interpreted. The mean age of the participants was 35.3±14.4 years. 88(47.31%) were males and 98(52.69%) were females (male to female ratio was 1: 1.1). Among 186 study subjects, E. coli (28.6%) was the most common isolated organism followed by Pseudomonas spp. (17.9%), Klebsiella (17%), Acinetobacter (15.2%), Staph. aureas (9.8%). Isolated Grampositive bacteria were resistant to amoxiclav (100%), azithromycin (90%) and all were sensitive to linezolid and vancomycin (100%). Isolated Gram-negative bacteria were resistant to cefixime (100%) followed by cefuroxime and levofloxacin (97%). Appropriate prophylactic therapy for any major surgeries reduces incidence of SSI, and thereby reduces morbidity, mortality and cost burden in patients. Mugda Med Coll J. 2025; 8(1): 29-35